2011
DOI: 10.1055/s-0029-1245799
|View full text |Cite
|
Sign up to set email alerts
|

Is a Routine Ultrasound in the Third Trimester Justified? – Additional Fetal Anomalies Diagnosed After Two Previous Unremarkable Ultrasound Examinations

Abstract: The ultrasound examination in the 3 rd trimester is of additional benefit and can detect previously unknown structural abnormalities. These findings are relevant for perinatal management and postnatal follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
(25 reference statements)
4
18
0
Order By: Relevance
“…Thus, it ensures prompt and timely postnatal intervention. Manegold-Brauer et al [13] also support our findings which found an increased rate of detection of fetal anomalies by a third-trimester scan. Hence, it is important not to skip fetal USG in the third trimester, which can help us find out renal anomalies requiring early postnatal intervention.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it ensures prompt and timely postnatal intervention. Manegold-Brauer et al [13] also support our findings which found an increased rate of detection of fetal anomalies by a third-trimester scan. Hence, it is important not to skip fetal USG in the third trimester, which can help us find out renal anomalies requiring early postnatal intervention.…”
Section: Discussionsupporting
confidence: 90%
“…In these situations, a specialized sonographic examination showing no additional malformations can be particularly reassuring. The overall detection rate of fetal abnormalities in our unit was shown previously to be 90% 12 . Nearly one‐third of our patients presented with polydactyly of a chromosomal origin: 5 of 7 with trisomy 13, either confirmed by chromosome analysis or clinically evident, and 1 with trisomy 18 (Table 2).…”
Section: Discussionsupporting
confidence: 58%
“…With the advance of non‐invasive prenatal screening for aneuploidies using cell‐free fetal DNA in maternal blood sample, there is a risk of ultrasound being considered to be less important in the first trimester. However, existing data suggest that at least 50% of malformations can be detected in a first trimester scan . Therefore, strategies providing a routine early malformation scan should be considered including the assessment for congenital contractures and fetal movement, as a significant number will already be present in the late first trimester.…”
Section: Resultsmentioning
confidence: 99%